Analytic probability distributions for snow‐dominated streamflow. Issue 5 (28th May 2013) - Schaefli, B.; Rinaldo, A.; Botter, G.
Key Points Analytic model for the probability distribution of snow‐dominated streamflow Stochastic framework to link precipitation (rain, snow) and streamflow dynamics 14 case studies confirm progress in statistical characterization of streamflow